Taquari River Basin: a basin of contrasts, environmental challenges, and ecosystem opportunities - Romullo Oliveira Louzada (2025)
River basins are geographically defined areas where water drains into a main river. These drainage systems mirror the environment, reflecting the interplay of physical factors such as relief, soil, geology, and hydrography, along with biological elements like vegetation and fauna. Consequently, disturbances in these systems trigger on-site impacts, which can escalate into off-site consequences downstream. Understanding how these impacts evolve over time and space and how they can be mitigated through compensatory ecosystem services (offsets) is the core focus of this study, which provides a comprehensive analysis of the Taquari River Basin in central-western Brazil. The Taquari River Basin is one of the most degraded watersheds in Brazil. It suffers from large-scale erosive processes in its upper region (UTRB) and excessive sedimentation in its lower reaches within the Pantanal wetlands. This sediment accumulation has led to river channel shifts (avulsion) and widespread flooding since the late 20th century. The study was divided into two sections: UTRB and the Pantanal to assess these environmental changes. A broad dataset, including remote sensing, spatial analysis, and statistical modeling, was used to investigate sediment dynamics and their impacts across the basin. A GIS-based Boolean algebra method revealed that 65% of the UTRB is at high or very high risk of soil loss, emphasizing the urgent need to stabilize gullies in the region. A complementary analysis using orbital remote sensing (optical and radar data) identified nearly 3,000 gullies, with 60% still active and only 2% stabilized, highlighting the necessity for immediate restoration efforts. Additionally, datasets from MapBiomas and the Rural Environmental Registry (CAR) underestimate exposed soil areas, suggesting the need for more precise land use classifications. A temporal analysis of exposed soil pixels from 1985 to 2024 revealed that soil exposure peaked in 2021 (3.4% of the UTRB) and decreased to 0.6% in 2024. By 2024, some of areas indicate a negative trend in bare soil pixels as a natural regeneration of vegetation process. However, factors such as commodity prices, climate variability, and environmental policies could influence this recovery trajectory. In the Pantanal, a fluvial avulsion model predicts the formation of a new river channel by 2080, reducing the flooded area and converting it into terrestrial land. This transition enhances soil fertility through organic matter accumulation, but it requires close monitoring to prevent negative outcomes such as deforestation and wildfires. The findings presented here provide a comprehensive assessment of the basin, offering insights for rural landowners facing erosion or flooding while also equipping public authorities with critical data for territorial planning. The study contributes to strategies for erosion control in the upper basin and the preservation of emerging ecosystem services in the Pantanal, particularly in terms of biodiversity conservation and carbon retention.